IBS survey 2010 drivers, barriers and critical success factors in adopting Industrialised Building System (IBS) construction by G7 contractors in Malaysia - Mohamad Kamar Kamarul Anuar, Azman Mohamed Nor Azhari, Mohd Nawi Mohd Nasrun, (N/A, 2014)
IBS survey 2010 drivers, barriers and critical success factors in adopting Industrialised Building System (IBS) construction by G7 contractors in Malaysia by Mohamad Kamar Kamarul Anuar, Azman Mohamed Nor Azhari, Mohd Nawi Mohd Nasrun,